Klotho enhances stability of chronic kidney disease atherosclerotic plaques by inhibiting GRK2/PLC-β-mediated endoplasmic reticulum stress in macrophages via modulation of the ROS/SHP1 pathway - Zhe Li; Jing Li; Lin Li; Qian Wang; Qian Zhang; Ling Tian; Chenchen Li (Scientific Reports)
Abstract Klotho has been importantly linked to atherosclerosis, but little is known about its specific role. This study investigates the mechanism by which Klotho enhances the stability of atherosclerotic plaques in chronic kidney disease. apoE-/- knockout mice and C57BL/6 mice underwent 5/6 nephrectomy and then klotho-NC and klotho-mimic groups were set up to be fed a high-fat chow diet and a dummy group was created to be fed a normal chow diet. qPCR detected relative mRNA expression of klotho. Oil Red O and HE staining assessed lipid proportion in the aorta. Masson staining evaluated renal failure pathology in mice. Immunohistochemistry measured MAC-2 and α-SMA expression in the aorta. ELISA quantified urea, cholesterol, calcium ions, and triglycerides in mouse plasma. Western blotting detected associated protein expression, followed by cell-based experiments for validation. Compared with the Klotho-NC group, the plaque area and aortic lipid and renal fibrosis area were reduced in the Klotho-mimic group. Klotho-mimic reduced macrophage area, plasma urea, cholesterol, calcium ions, and triglyceride levels, and decreased the expression of p-PERK, NOX2, NOX4, Caspase-3, Caspase-9, Bax, p-GRK2, p-PLCβ, p-Src, and p-IP3R. Without ox-LDL stimulation, Klotho expression increased in the Klotho-mimic group, with no significant differences in NOX2, p-SHP1, p-Src, p-PERK, p-GRK2, and p-PLCβ. With ox-LDL in high-calcium medium, Klotho and p-SHP1 increased, while NOX2, p-Src, p-PERK, p-GRK2, and p-PLCβ decreased in the Klotho-mimic group. After ox-LDL and TPI-1 treatment, Klotho increased, NOX2 decreased, and other proteins showed no significant changes. Adding shRNA-GRK2 reduced NOX2, p-Src, and p-PERK, increased p-SHP1, with no changes in p-GRK2 and p-PLCβ. Differences in NOX2, p-GRK2, p-PLCβ, and p-PERK between groups were reduced in high-calcium medium, while p-SHP1 differences increased. Klotho enhances chronic kidney disease atherosclerotic plaque stability by inhibiting GRK2/PLC-β-mediated endoplasmic reticulum stress in macrophages via the ROS/SHP1 pathway.